Efecto del nitrógeno en el contenido de proteína y saponina en quinua (Chenopodium quinoa Willd), adaptada en la zona norte de la provincia de Los Ríos - Campos Alvarado, Katiuska Del Rocio (2019)
Quinoa cultivation has great nutritional benefits, one of the most important being protein. The research was developed in the laboratory of bromatology of the Campus "La María" properties of the State Technical University of Quevedo, located at kilometer 7,5 of the Quevedo – El Empalme highway, canton Mocache, province of Los Ríos, genotype 0-3 September and October 2019. The variables established to study were: nitrogen concentration in grains (%), absorption of nitrogen in grain (Kg N ha-1), saponin determination (%), protein determination (%) nitrogen concentration in the soil (ppm). Using a completely randomized design (DCA) with 5 treatments and 5 repetitions.For the comparison of measures the Tukey test (5%), obtaining nitrogen concentration in the grains the T4 with 2.71%, absorption of grain nitrogen in the T4 with 173,88 Kg N ha-1, determination of saponin in the T4 with 0.19%, determination of protein in the tr T5 ties with 16,94% and T4 with 16,54%, while in nitrogen concentration in the soil the T4 with 63,67 ppm. This research has shown that Nitrogen positively affects the protein content in quinoa grains. Keywords: Andean grain, dynamic, fertilizer, grain, efficiency.